Guidelines for the pediatric patient with acute lymphoid leukemia in outpatient monitoring: toxicity profile and adherence to treatment (Research, Society and Development, 2019)
In the childhood population, an annual incidence of about 200,000 new cases of cancer is estimated worldwide, with leukemia being the most common type. With regard to nursing, this scenario demands the need for specific training of professionals working in pediatric oncology, in order to ensure safe and effective care. Given this scenario, taking into account the effects of treatment, the objective was to conduct guidelines after the medical consultation, reinforcing the most important information, aiming at the planning of an individualized care for pediatric patients with ALL in outpatient follow-up. The research consists of a longitudinal descriptive study. Evaluations of sixteen children were performed, fifteen of them with diagnosis of B-ALL and one with T-ALL, according to inclusion criteria, these are preliminary results. Regarding the most frequent toxicities, we must emphasize hematological as the most frequent and expected, taking into account the period of lower hematological cell count as a consequence of the drugs infused in the protocol BFM 2002 and GBTLI 2009. Other toxicities such as dermatological, gastrointestinal, hepatic and renal diseases should awaken close attention of professionals who are caring for the pediatric oncology patient. Another important aspect is the latent need of the nurses professionals to know and to master the graduation of the toxicities, guiding the care and the orientations from the classification of the CTCAE. The nurse should strive to elucidate and reinforce the information given by the physician and provide more information to the child and the family. It is also worth emphasizing that nurses' actions must be beyond practice and procedures, and that guidelines are as important as doing so in the search for an individualized, quality, humanistic and interdisciplinary care.